Dental pain behavior of children with autism spectrum disorder at the Biruku Foundation, Bandung City - Hanna Asshabirina Wanazizah; Sri Susilawati; Inne Suherna Sasmita (Wolters Kluwer Medknow Publications, 2022)
Background: Dental pain is one of the most common symptoms of dental and oral problems that are generally identified by verbal self-reports; however, it is difficult for children with autism spectrum disorder (ASD) who have social communication deficits. Dental pain in children with ASD can be detected by specific behavioral changes. Objective: In this study, the aim was to determine the dental pain behavior of children with ASD at the Biruku Foundation, Bandung City. Methods: The descriptive method used a cross-sectional design approach. The study sample consisted of children with ASD who were diagnosed by pediatricians as high-functioning autism (HFA) or low-functioning autism (LFA) and who were experiencing dental caries as a factor causing dental pain, which was observed by the examination of 12 children by a total sampling technique. Data collection was conducted in the form of a Dental Discomfort Questionnaire (DDQ). Results: High DDQ scores were obtained for three children (25%), a moderate DDQ score for seven children (58.3%), and a low DDQ score for two children (16.7%). The most frequent dental pain behavior displayed by children with ASD at the Biruku Foundation was increased saliva production (8.8%). Conclusion: Dental pain in children with ASD at the Biruku Foundation, Bandung City fell into the moderate category.